2011
DOI: 10.1089/scd.2010.0263
|View full text |Cite
|
Sign up to set email alerts
|

Stromal-Derived Factor-1/CXCR4Signaling: Indispensable Role in Homing and Engraftment of Hematopoietic Stem Cells in Bone Marrow

Abstract: Homing and engraftment of hematopoietic stem/progenitor cells (HSPCs) in bone marrow is the major determining factor in success of hematopoietic stem cell transplantation. This is a complex, multistep process orchestrated by the coordinated interplay between adhesion molecules, cytokines, growth factors, and regulatory cofactors, many of which remain to be defined. Recent studies have highlighted the pivotal role of unique stromal-derived factor-1 (SDF-1)/CXCR4 signaling in the regulation of HSPC homing and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 146 publications
(159 reference statements)
3
99
1
1
Order By: Relevance
“…Although some recent studies have questioned the role of CXCR4 in HSC homing in fetal liver hematopoiesis [31] and CXCR4-overexpression studies [32], it is commonly accepted that the CXCR4/CXCL12 axis plays a significant role in the BM homing of transplanted HSPCs [33,34]. Consistent with the role of CXCR4 in HSC homing, we observed that b7KO HSCs were impaired in their ability to migrate toward CXCL12 in vitro and home to BM in vivo (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Although some recent studies have questioned the role of CXCR4 in HSC homing in fetal liver hematopoiesis [31] and CXCR4-overexpression studies [32], it is commonly accepted that the CXCR4/CXCL12 axis plays a significant role in the BM homing of transplanted HSPCs [33,34]. Consistent with the role of CXCR4 in HSC homing, we observed that b7KO HSCs were impaired in their ability to migrate toward CXCL12 in vitro and home to BM in vivo (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…7 Strong CXCL12 expression by CD271 þ ALP þ MSCs could be a source of abnormal survival/proliferation signaling for adjacent neoplastic CD34 þ HSPCs. CXCL12 is also involved in hematopoietic stem cell homing, 27 and isolated CD34 þ HSPCs from MDS patients are impaired in their ability to migrate toward CXCL12, 51 a finding that is associated with increased susceptibility to apoptosis in vitro. 28 Increased CXCL12 expression by MSCs could be part of a defective feedback loop between neoplastic CD34 þ HSPCs and altered MSCs in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…24 Finally, we examined CXCL12 expression because the so-called CXCL12-abundant reticular cells (termed CAR cells) contribute to HSPC maintenance and proliferation in mouse models; 25 CXCL12 signaling is also implicated in HSC homing and the pathophysiology of MDS in in vitro studies. [27][28][29] Adult human bone marrow consists of parenchyma, hematopoietic elements admixed with variable amounts of fat; trabecular bone, thin layers of bone lined by predominantly quiescent osteoblasts; and vasculature. 30 Herein, we refer to zones within the bone marrow microenvironment as perivascular when they are predominantly distributed within B10-20 mm of vessels; trabecular when immediately adjacent to trabecular bone or bone-lining cells; and parenchymal when diffusely admixed with hematopoietic elements or adipocytes.…”
mentioning
confidence: 99%
“…However, the low homing and engraftment efficiency of HSPCs act as a limiting factor in wide range implications and success of hematopoietic stem cell transplantation (HSCT). 1 Gene knockout studies of SDF-1 and CXCR4 as well as transfusion of human HSPCs in murine recipients revealed the principle role of SDF-1/CXCR4 signaling in homing and engraftment. [2][3][4][5] CXCR4 (a G protein coupled receptor) is expressed on surface of HSPCs which upon binding to its ligand SDF-1, switches to active conformation, highly permissible for interaction to G protein and other downstream effectors, thus resulting in CXCR4 downstream signaling.…”
Section: Introductionmentioning
confidence: 99%